One new species and one poorly known species of Neoperla in the montivaga group (Plecoptera: Perlidae) from Hainan Province, China - Mo, Raorao; Wang, Guoquan; Li, Weihai (Zootaxa, 2021)
One new species of the genus Neoperla in the montivaga species group, N. limushana sp. nov. is proposed from Hainan Province of southern China. The new species is compared with related congeners of the group. In addition, a supplementary description and illustrations of the adult male of N. hainanensis Yang & Yang, 1995 also presented. A provisional key to the presently known species of the N. montivaga group of Hainan Province is also given.